12-Item Pruritus Severity Scale: Development and Validation of New Itch Severity Questionnaire. (2nd October 2017) - Reich, Adam; Bożek, Agnieszka; Janiszewska, Katarzyna; Szepietowski, Jacek C.
Abstract : Introduction . A validated assessment of pruritus intensity is an important but still difficult clinical problem due to a subjective nature of this sensation. Objective . The aim of this study was the creation and validation of new itch severity questionnaire assessing pruritus intensity. Material and Methods . A total of 148 patients with pruritic dermatoses were asked to assess pruritus intensity using 12-Item Pruritus Severity Score (12-PSS) and Visual Analogue Scale (VAS). Patients were also asked to complete the Dermatology Life Quality Index (DLQI) and Hospitality Anxiety and Depression Scale (HADS). Test-retest comparison of 12-PSS was conducted in 102 subjects who completed the itch questionnaire twice with the 3- to 5-day interval. Results . We have created the 12-PSS assessing pruritus intensity (two questions), pruritus extent (one question) and duration (one question), influence of pruritus on concentration and patient psyche (four questions), and scratching as a response to pruritus stimuli (four questions). A maximum scoring was 22 points. The results showed strong consistency (Cronbach α coefficient 0.81). A significant correlation was observed with VAS (r = 0.58, p < 0.001 ) and quality of life level according to DLQI (r = 0.53, p < 0.001 ). Test-retest comparison in 102 subjects revealed a satisfactory reproducibility of achieved results (ICC = 0, 72). Conclusions . The newly developed pruritus severity questionnaire may be used in daily clinical practice in the future.